2020
DOI: 10.1177/1039856219891637
|View full text |Cite|
|
Sign up to set email alerts
|

Medical student perceptions of physical and emotional safety before and after 5-week mental health placements

Abstract: Objective: Understanding whether medical students feel safe in mental health placements is important to delivering effective and engaging training experiences. Method: Second year students completed anonymous online surveys before ( n = 37) and after ( n = 41) mental health placements, to gather qualitative and quantitative data about their sense of physical and emotional safety, and factors that positively and negatively influenced their experiences. Data were analysed using chi square and content analysis. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Medical students learn at a time of developmental challenge as they accept increasing social roles and obligations, as well as some experiencing their own mental health problems (Arnett, 2007). Some find themselves emotionally taxed in responding to people in psychological distress (Gallan et al, 2020). The multimedia resource promotes active learning experiences as clinical teachers and peers role-model expectations that students transitioning into medical professionals have a definite role in interacting with and relating to people with mental distress who are thinking about suicide (Monrouxe, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Medical students learn at a time of developmental challenge as they accept increasing social roles and obligations, as well as some experiencing their own mental health problems (Arnett, 2007). Some find themselves emotionally taxed in responding to people in psychological distress (Gallan et al, 2020). The multimedia resource promotes active learning experiences as clinical teachers and peers role-model expectations that students transitioning into medical professionals have a definite role in interacting with and relating to people with mental distress who are thinking about suicide (Monrouxe, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Chaung, Seung-Kyo 1) • Shin, Yun Hee 2) • Kang,Youngmi 3) • Choi, Dongwon 4) • Jeong, Hye Sun 5) • Song, Youngshin 6) • Kim, Hyun-Ju 7) • Kim, Ji-Su 8) • Sohng, Kyeong-Yae 9) • Park, Hyoung Sook 10) • Park, Soohyun 11) 기본간호학회지 28(3), 2021년 8월…”
Section: )mentioning
confidence: 99%
“…1 Whilst the authors concluded that safety frameworks should be established pre-placement, I argue that medical schools must go beyond this and provide more thorough pre-clinical training in mental health literacy (MHL) and clinical psychiatry. 1…”
mentioning
confidence: 99%
“…Whilst Gallan et al found that 51.35% of medical students had some concerns regarding their physical safety pre-placement, no student reported feeling physically unsafe in the post-survey. 1…”
mentioning
confidence: 99%
See 1 more Smart Citation